Information System Requirements Analysis for MSME Digitalization Using the SDLC Waterfall Approach - Alvan Dhan; Angelina Apriyani Pandiangan; Nadita; Ratih Echa Kurnia; Rafi Akmal Rizqullah (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly mobile vendors in the food and service sectors, face operational challenges such as manual transaction recording, limited customer reach, and unstructured order management. This study aims to analyze and design an information system that supports MSME digitalization based on real user needs. The research adopts the Software Development Life Cycle (SDLC) using the Waterfall model, limited to the analysis and design stages. Data were collected through literature review and semi-structured interviews with mobile MSME vendors. The findings highlight key issues related to transaction management, product updates, and customer interaction in dynamic environments. Based on these findings, functional requirements were formulated, including features for product management, order processing, digital transactions, and sales reporting. The system design is modeled using Unified Modeling Language (UML), including use case, activity, and class diagrams. The proposed system design provides a structured and practical solution aligned with MSME operational needs, with the potential to improve efficiency, expand market reach, and support better business decision-making.